Fruits and vegetables dietary intake and its estimated consumption among adults receiving antiretroviral therapy in health facilities in Northcentral Ethiopia: a multi-facility cross-sectional study - Boneya, Dube Jara; Ahmed, Ahmed Ali; Yalew, Alemayehu Worku; Gebremedhin, Samson (Frontiers in Nutrition, 2024)
Background Despite the significant role of fruit and vegetables (FAVs) in preventing a variety of chronic diseases and their potential to bolster immune responses and slow the progression of HIV infection to AIDS, there is a lack of studies on the dietary intake of FAVs among HIV-infected adults in Africa, including Ethiopia. Hence, this study aimed to investigate the magnitude of FAV intake and estimated consumption among HIV-infected adults receiving antiretroviral therapy (ART) in northcentral Ethiopia. Methods A multifacility cross-sectional study was conducted on the FAV intake among 865 HIV-infected adults receiving ART. A Poisson regression model with robust variance was used to identify factors associated with FAVs dietary intake. Results The study indicated that 655 (76.34%; 95% CI: 73.38, 79.07) HIV-infected adults reported consuming FAVs less than once per day, with 838 (97.67%, 95% CI: 96.41, 98.49) and 676 (78.79%, 95% CI: 75.92, 81.40) HIV-infected adults reporting consuming fruits and vegetables less than once per day, respectively. The median (IQR) total FAV intake was 271.3 (IQR: 92.5, 439.5) g/day, with the median (IQR) intake of fruits being 248.1 (IQR: 100.0, 400.0) g/day and vegetables being 273.78 (IQR: 82.44, 348.33) g/day, respectively. We found that being divorced (APR = 1.57, 95% CI: 1.16, 2.12), employed as a daily laborer (APR = 2.08, 95% CI: 1.36, 3.20), being employed (APR = 1.77, 95% CI: 1.10, 2.84), merchants (APR = 1.59, 95% CI: 1.03, 2.47), having children as caregivers (APR = 1.61, 95% CI: 1.02, 2.55), an advanced WHO clinical stage (APR = 1.32, 95% CI: 1.32(1.03, 1.69), and receiving ART for more than 8 years (APR = 1.78, 95% CI: 1.18, 2.67) were found to be independent predictors of FAV dietary intake among HIV-infected adults. From the findings, we understood that farmers were less likely to consume FAVs compared to employed individuals, daily laborers, and merchants. Conclusion The finding indicated a very low level of FAV dietary intake among HIV-infected adults receiving ART, falling well-below the minimum recommendation for physically active adults. Despite living in areas with surplus production and producing these items, farmers are less likely to consume FAV. The study emphasizes the importance of focusing on the early stage of ART treatment for patients and family therapy, including counseling and guidance on consuming healthy diets such as FAVs, to enhance the role of children as caregivers for their families. Additionally, there is a need for comprehensive nutritional counseling to improve FAV consumption, with a particular emphasis on educating individuals about portion size estimation for the consumption of FAVs.